2013
DOI: 10.1093/jjfinec/nbt006
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Asymmetric Comovements of International Stock Market Returns

Abstract: Based on a new approach for measuring the comovements between stock market returns, we provide a nonparametric test for asymmetric comovements in the sense that stock market downturns will lead to stronger comovements than market upturns. The test is used to detect whether asymmetric comovements exist in international stock markets. We find the following empirical facts. First, asymmetric comovements exist between the United States (U.S.) stock market and the stock markets for Canada, France, Germany, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 23 publications
0
21
0
1
Order By: Relevance
“…6, No. 3;2014 estimated Gaussian copula correlations between the three markets are different from their linear correlations in Table 1. Specifically, the correlation between the equity market and bond market is approximately 0.08, decreased by 3.2 % as compared to its linear correlation.…”
Section: The Australian Marketsmentioning
confidence: 69%
See 3 more Smart Citations
“…6, No. 3;2014 estimated Gaussian copula correlations between the three markets are different from their linear correlations in Table 1. Specifically, the correlation between the equity market and bond market is approximately 0.08, decreased by 3.2 % as compared to its linear correlation.…”
Section: The Australian Marketsmentioning
confidence: 69%
“…6, No. 3;2014 peaked and have fatter tails than normal distribution. Intuitively, all se-ries show excess kurtosis, ranging from 4.7 to 104.5, in which the Australian money market series displays the highest kurtosis.…”
Section: Datamentioning
confidence: 97%
See 2 more Smart Citations
“…On the other hand, in the volatility spillovers, the skewness was relevant just in what occurs between France and the United Kingdom. Several empirical studies also found the existence of asymmetric co-movements in international capital markets of developed countries, such as Koutmos & Booth (1995), Li (2014), among others. Nevertheless, contrary to this study results, some studies found this effect between developing and developed markets - Pagán & Soydemir´s (2001) and Rejeb & Arfaoui´s (2016) identified this phenomenon specifically between the countries of Latin America.…”
Section: Interdependence Phenomenon and Asymmetriesmentioning
confidence: 96%